DESAIN DAN 3D PRINTING PADA PENGUATAN PEMBELAJARAN BERBASIS PROYEK SMKN 2 CIREBON - Noviyanti, Anastasia; Yudha Prakasa, Danang; Saptari Saldi, Zaki; Fariz Akbar, M. Salman; Canvin Santana, Fillberto (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Community service activities were carried out by the Prasetiya Mulya University team combining Human-Centered Design (HCD) and 3D printing (3DP) technology to improve the capacity of teachers at SMK Negeri 2 Cirebon in implementing Project-Based Learning (PjBL). Project-Based Learning combined with HCD helps educators guide students in creating innovative products that are relevant to user needs, while 3DP facilitates the prototyping process in a cost-effective and accessible way. The training was conducted in four thematic sessions covering entrepreneurship, creativity and innovation, introduction to HCD, and hands-on 3D printing practice. Evaluation of the activities was carried out through pre- and post-tests as well as participant reflections. Results showed an average improvement of 24%, increasing from 28% to 52%, indicating that the training effectively improved participants’ understanding. Despite technical challenges related to design software, practical approaches using physical product simulations were successfully implemented. The findings suggest that integrating HCD and 3DP enhances teachers’ ability to conduct contextual, creative, and technology-adaptive project-based learning. This program also provides a foundation for future mentoring to ensure sustainability and broader implementation in vocational education